PENGARUH MOTIVASI BELAJAR DENGAN MENGGUNAKAN MODEL KUANTUM TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Deby Fauzi Asidiqi (Journal of Professional Elementary Education, 2022)
The  purpose  of  this  study  was  to  determine  the  influence  of  motivation  on learning outcomes of students that using quantum learning model with the direct learning model. The method that used in this research was a quasi experimental with research design nonequivalent control group design.  The  sampling  technique  in  this  research  was  using  cluster random sampling technique. In this research, experiment class using quantum learning model and the control class using direct learning model. The  research  instrument  was  given  in  the  form  of  10  essay  questions.  Data analysis techniques to test the hypothesis were using correlation and linearity (simple  regression).  From  the  calculation  of  the  hypothesis  test  obtained correlation r ≤ +1, 0.9032 ≤ +1, thus there is a significant  functional  relationship  between  the  variables  of  motivation  and learning outcomes of  students who  using  quantum  learning model.  From  the calculation of the linearity hypothesis test (simple regression) obtained Fhitung > Ftabel, 172.68 > 4,09, thus there is a significant functional effect between varaibel motivation and learning outcomes of students who using quantum learning model